IL-33/ST2 Pathway as a Rational Therapeutic Target for CNS Diseases. (15th January 2018) - Du, Li-Xia; Wang, Yan-Qing; Hua, Guo-Qiang; Mi, Wen-Li
Highlights: IL-33 can be cleaved by mast cells, neutrophils or macrophage-derived proteases. IL-33 exerts its effects through the receptor complex of ST2 and IL-1RAcP. IL-33 and ST2 are expressed in the CNS although the cellular distributions are still controversial. IL-33/ST2 signaling plays a dual role in many central nervous system diseases. Abstract: Interleukin (IL)-33 is a member of the interleukin-1 cytokine family that is produced by many different types of tissues including the central nervous system (CNS). IL-33 mediates its effects via its heterodimeric receptor complex, comprised of ST2 and the IL-1 receptor accessory protein (IL-1RAcp). As a pleiotropic nuclear cytokine, IL-33 is a crucial factor in the development of cardiovascular diseases, allergic diseases, infectious diseases, and autoimmune diseases. Recently, accumulated evidence shows that the IL-33/ST2 axis plays a crucial and diverse role in the pathogenesis of CNS diseases, including neurodegenerative diseases, cerebrovascular diseases, infectious diseases, traumatic CNS injury, chronic pain, etc. In this review, we discuss the recent findings in the cellular signaling of IL-33 and advancement of the role of IL-33 in several CNS diseases, as well as its therapeutic potential for the treatment of those diseases.